God help the child - Morrison, Toni. (London : Chatto & Windus, 2015)
A tale about the way the sufferings of childhood can shape, and misshape, the life of the adult. At the center: a young woman who calls herself Bride, whose stunning blue-black skin is only one element of her beauty, her boldness and confidence, her success in life, but which caused her light-skinned mother to deny her even the simplest forms of love. There is Booker, the man Bride loves, and loses to anger. Rain, the mysterious white child with whom she crosses paths. And finally, Bride’s mother herself, Sweetness, who takes a lifetime to come to understand that "what you do to children matters. And they might never forget."
"This is a Borzoi book."
AAL
Complimentary copy
Keywords: African Americans -- Fiction; Mothers and daughters -- Fiction